Rumah Pintar Mosso Anak Ujung Negeri - Irianto Irianto; Iis Roin Widiati; Reni Rochmawati; Didi S.S. Mabui; Sitti Fatimah (Jurnal Pengabdian Masyarakat Hasanuddin (JPMH), 2022)
Jayapura City is also a border area with foreign countries. In this city there is a village that is at the very end and directly borders the country of Papua New Guinea, namely Kampung Mosso. This village lacks educational facilities and infrastructure. This causes people's literacy skills are still lacking.The Mosso Children's Reading House in Ujung Negeri is an activity to build a library or reading garden at PAUD Florencia and PKBM (Center for Community Learning Activities) and provide lessons to children aged 4-12 years who have dropped out of school or are illiterate communities in Mosso Village, Muara Tami District, Jayapura City.The library will be opened six times a week, every Monday to Saturday, as well as mentoring activities will be held five times a week, every Monday to Friday, for 6 weeks. All activities from library construction to the mentoring process as well as the teaching and learning process were carried out by the team together with volunteers in the activities of the Ujung Negeri Mosso Children's Reading House. This activity is an effort made by Yapis Papua University students and is clear evidence that Yapis Papua University contributes to improving the quality of human resources in the community of Mosso Village, Jayapura City, NKRI - PNG Border.